2008
DOI: 10.2196/jmir.1114
|View full text |Cite
|
Sign up to set email alerts
|

Weight, Blood Pressure, and Dietary Benefits After 12 Months of a Web-based Nutrition Education Program (DASH for Health): Longitudinal Observational Study

Abstract: Background The dietary habits of Americans are creating serious health concerns, including obesity, hypertension, diabetes, cardiovascular disease, and even some types of cancer. While considerable attention has been focused on calorie reduction and weight loss, approaches are needed that will not only help the population reduce calorie intake but also consume the type of healthy, well-balanced diet that would prevent this array of medical complications.Objective To design an Internet-based nutrition education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
79
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 17 publications
4
79
0
3
Order By: Relevance
“…Based on self-recorded surveys about food, participants reported that they began a diet rich in fruits, vegetables, and grains, as well as reducing the consumption of carbonated drinks. 59 In another investigation lasting 12 weeks, patients with diabetes sent daily messages via the internet or mobile phone with their glucose levels, and every week the nurses responded with ideal and individual recommendations for each patient through short, simple, and direction information. Constant messaging contributed to greater adherence to treatment, the practice of physical exercises and foot care.…”
Section: New Technological Approachesmentioning
confidence: 99%
“…Based on self-recorded surveys about food, participants reported that they began a diet rich in fruits, vegetables, and grains, as well as reducing the consumption of carbonated drinks. 59 In another investigation lasting 12 weeks, patients with diabetes sent daily messages via the internet or mobile phone with their glucose levels, and every week the nurses responded with ideal and individual recommendations for each patient through short, simple, and direction information. Constant messaging contributed to greater adherence to treatment, the practice of physical exercises and foot care.…”
Section: New Technological Approachesmentioning
confidence: 99%
“…They also reported similar findings in another dietary intervention study on type 2 diabetes mellitus patients (21) . Furthermore, Moore et al showed that participating in an Internet-based nutrition education programme on the DASH diet could result in significantly reduced body weight after 12 months (22) .…”
mentioning
confidence: 99%
“…23 To the best of our knowledge there has only been a single study that previously evaluated the efficacy of the original DASH diet with no other behavioral modifications in a free-living environment on individuals who follow a typical American diet. 16 That previous study utilized an internet-based instructional method whereas the present study uses a traditional person-to-person instructional technique. Presently, individuals following the DASH diet in a free-living environment exhibited a significantly greater reduction in SBP relative to controls; however, DBP was not significantly altered in either group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite, the success of the clinical feeding trials 10,13 and subsequent clinical interventions combining the DASH diet with other behavioral modifications, 14,15 the ability of adopting the original DASH diet followed in a free-living environment where no pre-measured meals are provided and without any additional behavioral modifications has only been evaluated in a single study. 16 This previous study assessed the effect of an internet-based nutrition education program, which was based on the DASH diet, on body weight and blood pressure over 12 months. While this intervention resulted in significantly reduced body weight and blood pressure, only 26% of the participants who began the program, completed all 12 months.…”
mentioning
confidence: 99%